Особливості врегулювання крос-культурних конфліктів у процесі здійснення зовнішньоекономічної діяльності - Подра, О. П.; Лиса, Д. С.; Podra, O. P.; Lysa, D. S. (Видавництво Львівської політехніки, 2023)
Досліджено сутність та особливості крос-культурної бізнес-комунікації, визначено причини виникнення конфліктів у процесі крос-культурної бізнес-взаємодії в умовах здійснення зовнішньоекономічної діяльності. Проаналізовано класифікацію ділових культур Річарда Льюїса, описано їх поділ на мультиактивні, лінійно-активні та реактивні, визначено їх характеристики. Охарактеризовано процес вирішення міжкультурних конфліктів з виокремленням ключових етапів. Досліджено заходи врегулювання кроскультурних конфліктів, а саме: вирішення всередині компанії, залучення третіх сторін та спеціалізовані форми. Розроблено рекомендовану стратегію врегулювання кроскультурних конфліктів у компанії в процесі здійснення зовнішньоекономічної діяльності, що передбачає реалізацію семи послідовних етапів.

Any violations or problems in the establishment of cross-cultural communication in the organization can become the causes of potential conflicts. Therefore, for their prevention or faster solving, it is important to understand the possible causes of their occurrence. Problems related to the establishment of cross-cultural communication can be: the use of cultural filters when forming an opinion about foreign counterparties; insufficient level of tolerance towards partners or clients; incorrect use of verbal and non-verbal means of communication; the establishment of new connections may depend on the degree of implementation of the principles of social responsibility, as this indicates the reliability of the business entity. Conventionally, all problems of cross-cultural interaction can be divided into two groups: conducting negotiations with international business partners and communication within the organization. Usually, cross-cultural conflict during business negotiations arises for two main reasons. First, when dealing with cultural differences, partners quite often rely on stereotypes. Stereotypes are often derogatory and can lead to distorted expectations about the opponent’s behavior and potentially misinterpretations. The second most common cause of intercultural misunderstandings is the tendency to interpret the behavior, values, and beliefs of others through the lens of one’s own culture. To overcome this tendency, it is important to learn as much as possible about the culture of the foreign partner’s side. The classification of business cultures by Richard Lewis can help to better navigate the characteristics of different cultures, comparing one with another and identifying common and distinctive features. This method is useful for planning cooperation with new counterparties in order to minimize the risk of potential conflicts due to unfamiliarity with the foreign partner. Before starting each negotiation, especially if they take place with new counterparties, it is necessary to process an array of information about cross-cultural differences. It is thanks to this measure that the probability of cross-cultural conflict can be minimized. And when a dispute arises, the company’s team still needs to review its training, because in most cases, knowing cultural characteristics and being able to use them correctly is the key to solving the problem. For the effective resolution of conflicts, it is worth using the recommended strategy for resolving cross-cultural conflicts in the company in the process of foreign economic activity.
Peculiarities of cross-cultural conflicts solving in the process of foreign economic activity implementation
Keywords: крос-культурна бізнес-взаємодія; комунікація; конфлікт; стратегія; cross-cultural business interaction; communication; conflict; strategy; 316.77; 339(075.8)